RISET EVALUASI PASAR KAGET DI KOTA BATAM - Tiurniari Purba (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
This study aims to determine what, who and how the shocked market in the Batam operate in accordance with research methodology used in research that is the method of evaluation research. The model used in this study is the CIPP evaluation, the model is analyzes the four dimensions of context dimension, input dimension, process dimension and product dimension. Batam city consists of 12 districts, there are only nine districts have 27 markets shocked. In this study, geographically dispersed market was dominated by Batu Aji sub-district with 10 markets in shock following Sekupang with five markets, while Sagulung four and Batam Kota had two shock markets. For District Nongsa, Batu Ampar, Bengkong, Sei Beduk, Lubuk Baja, each one market. The results of the evaluation obtained from this study is that the most needed by traders in the shock market is the attention and action of the local government. Attention in this regard is the support and proper facilities that can ultimately improve and develop the local economy concerned.